Material Characteristics Test for Electromedical Prototype Using Radiographic Image Analysis - Agatha Mahardika Anugrayuning Jiwatami (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2026)
The research conducted is the development of a phantom used for testing materials commonly used for electromedical prototypes. The research method used is Research and Development (RnD). Phantoms are made from acrylic and use Nylon, Iron, Stainless Steel, Galvanized, Aluminum, and Acrylic materials, as well as Medium Density Fiberboard (MDF). The phantom is then tested with a radiography system and exposed to voltage variations of 60 kV, 70 kV, and 80 kV. The best image results are when using a voltage of 80 kV. The results obtained, the image can distinguish materials with high and low absorption coefficients. Materials with high absorption coefficients such as Iron, Stainless Steel, Galvanized and Aluminum are good when used for electromedical prototypes that require movement in their working methods.